Impact of Storage Methods on Sweet Potato Spoilage in Plateau State Nigeria - Oludare Adedire; Godfrey Onuwa; Chinaka Walter John; Afolabi Ola Oladejo; Jacob Jepthah Mbah; Yahaya Sadiku; Vihi Samuel Keghter (International Journal on Food, Agriculture and Natural Resources, 2023)
Spoilage of sweet potato could be enormous when inadequate methods of storage are used. This research investigated impact of methods of storage on spoilage of sweet potato in three major markets of Plateau State Nigeria.  Data for the study were obtained from sellers  of sweet potato in Yan Doya market, New market and Farin Gada market of Plateau State through administration of questionnaires. Analysis of the data was carried out using descriptive statistics, Pearson Product Moment Correlation (PPMC), F-test statistics, t-test and Multiple Linear Regression (MLR) with backward elimination procedure.  Results from descriptive statistics showed that majority of sweet potato sellers adopted use of sack for storage of their goods. The second method commonly used for storage of sweet potato in the study area was found to be root cellar method. Pair-wise application of PPMC indicated that spoilage of sweet potato was positively correlated with adopted methods of storage which suggested existence of relationship among the variables. Analysis using F-test statistics indicated that the relationship did not occur by chance between the variables hence t-test aided determination of which independent variables mainly influenced the dependent variable of the study. From the use of MLR with backward elimination procedure, spoilages from sacks and root cellars methods were the independent variables which mainly influenced the total spoilage of sweet potato in Plateau State Nigeria. Therefore, policy holders in Plateau State need to offer agricultural extension services that would provide modern storage facilities or educate sellers of sweet potato on best way to use both basket and root cellar methods which were their adopted methods commonly  used for storage  of sweet potato.